Review of the literature on the dangers of zolpidem use, its potential for abuse and addiction - Skowrońska, Katarzyna; Chmura, Anna; Pondel, Kamil; Cyboran, Katarzyna; Baciur, Patrycja (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work : Commonly Z-drugs, especially zolpidem , are considered safer than short-acting drugs benzodiazepines . Recently, more and more is said about the abuse of these relatively harmless drugs. The aim of this study is to collect scientific reports on the increasing abuse of these drugs. State of knowledge: There are many reports of zolpidem abusers and addicts in the available literature . These people belong to three groups of patients: the first is people with insomnia who develop tolerance, the second is recreational use, and the third is people with mental disorders. Taking increased doses of zolpidem causes a psychostimulant effect, increased activity during sleep, up to delusions and psychotic symptoms. Rapid discontinuation of high doses of the drug should be performed in a hospital setting. Summary : Physicians should be advised to remain vigilant during therapy with group Z drugs and to check that the patient is not receiving the drug from multiple sources and is not taking zolpidem in supra-therapeutic doses .